5f-3(f-5)=4f-7

Simple and best practice solution for 5f-3(f-5)=4f-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5f-3(f-5)=4f-7 equation:


Simplifying
5f + -3(f + -5) = 4f + -7

Reorder the terms:
5f + -3(-5 + f) = 4f + -7
5f + (-5 * -3 + f * -3) = 4f + -7
5f + (15 + -3f) = 4f + -7

Reorder the terms:
15 + 5f + -3f = 4f + -7

Combine like terms: 5f + -3f = 2f
15 + 2f = 4f + -7

Reorder the terms:
15 + 2f = -7 + 4f

Solving
15 + 2f = -7 + 4f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-4f' to each side of the equation.
15 + 2f + -4f = -7 + 4f + -4f

Combine like terms: 2f + -4f = -2f
15 + -2f = -7 + 4f + -4f

Combine like terms: 4f + -4f = 0
15 + -2f = -7 + 0
15 + -2f = -7

Add '-15' to each side of the equation.
15 + -15 + -2f = -7 + -15

Combine like terms: 15 + -15 = 0
0 + -2f = -7 + -15
-2f = -7 + -15

Combine like terms: -7 + -15 = -22
-2f = -22

Divide each side by '-2'.
f = 11

Simplifying
f = 11

See similar equations:

| -413.4=-14.9n | | 4.5x+2.5x=35 | | 8-0.375x=-4 | | 474748659575757585r/r=15 | | 6a^2=7a | | 5-11=n | | 6x=4x+5 | | 20.50=2.75+4.00 | | 24p-18=2(6p+15) | | 4x+9y+20=0 | | 9-2(x+3)=5x+4 | | 3z=18-42 | | G(2x)=x^2+6 | | 48x^2+128=0 | | 26-3(x+4)=11-4(x+1) | | -5a+6=-4+-7 | | 4.00+2.75=20.50 | | 3(2x+1)-2(5-x)=29 | | 8y-8=4y+4 | | .06z=4.25 | | 2/5*8=z | | 9(3u+11)-14=11u-41-2u | | b^2+15+54=0 | | 2x=4x+7 | | 26-2x=26+2 | | x^2+56=0 | | u^2+6u+13=0 | | 14=2s+10 | | 4x-6=-8 | | -30-5x+7x=8 | | 1.2-x+3.2=x-4 | | 1/5*2=x |

Equations solver categories